Prevalence of Shoulder Pain Disability among Assistive Device Users with Paraplegia - Acharya, Bushnu Dutta; Rawal, M.; Rokaya, P.K.; Karki, D.; Limbu, D.; Binaya, P.L. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: To identify the prevalence of shoulder pain disability in paraplegic patients using assistive devices following Spinal Cord Injury.Methods: This was a cross-sectional study done among 53 SCI paraplegia patients having shoulder pain after use of assistive devices. Pre-test was done among 5 subjects. The association among different variables with shoulder was tested by using chi-square test. SPSS version 16 was applied to find the result.Results: The study showed that almost 98.11% of the respondents had shoulder pain with the assistive device users. Among them all of the participants were using wheelchair as the assistive devices and 86.3% had mild disability, 11.8% moderate disability and 2% sever disability. Among them, 72% of the patients had stayed in the hospital for less than six months. Shoulder pain was dependent on age, gender, duration of assistive devices used, type of assistive devices used and level of injury.Conclusions: Shoulder pain is common and has a high prevalence rate in both traumatic as well as non-traumatic spinal cord injury. Wheelchair user have more shoulder pain then other assistive devices users. Shoulder pain has a negative effect on activities of daily living and is a potential cause of activity limitations.